The global gender gap in innovation and creativity : an international comparison of the gender gap in global patenting over two decades - Carpentier, Elodie; Raffo, Julio (World Intellectual Property Organization, 2023)
This report examines the participation of women inventors in international patent applications from 1999 to 2020 and reveals that women were involved in the inventions behind only 23 percent of all applications, while men were involved in 96 percent. Consequently, women represent only 13 percent of all inventors listed in these filings, with an estimated contribution equivalent to only 10 percent of all PCT applications. Although women's participation in patenting has increased over time, achieving gender parity will require considerable effort. Based on current trends, if the inclusion conditions of the past five years persist, women may reach the 50 percent target for inventors around the year 2061. Women's participation in patenting varies considerably across world regions, sectors, and industries. Women inventors are predominantly concentrated in specific industries, such as biotechnology, food chemistry, and pharmaceuticals, whereas fields related to mechanical engineering have far fewer women inventors. Women inventors are more prevalent in academia (21 percent) than in the private sector (14 percent), but patent applications originating from academia represent only a small share of the total. Although the technological specialization of countries significantly alters the ranking for a few of them, for most countries, their technological specialization is not the primary factor in the gender gap in patents. The report also notes that women typically work in mostly-male teams and are more likely to work alone than in teams of women, including all-women teams or teams where they are the numerical majority. The decline in the proportion of patents from lone male inventors explains much of the positive trend in global inclusion over the last two decades. The report concludes that although women's participation in patenting is increasing, greater efforts are necessary to address the underrepresentation of women in innovation and patenting.
Keywords: Women inventors.; Patents.